For Programmers, Multicore Chips Mean Multiple Challenges. - Geer, David (Computer (00189162), 2007)
The article reports on the development of multicore microprocessor chips, which circumvents the challenge of packing ever more and smaller transistors onto single-core chips. This has created a challenge, however, for software developers, because rewriting existing applications to work on multicore chips is costly and time-consuming, and programmers can't create new applications for the multicore chips as fast as the chipmakers can make them. Some experts think a new programming language might be necessary to make the most of multicore capabilities.